2022
DOI: 10.1007/s00330-022-09355-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning assisted contrast-enhanced CT–based diagnosis of cervical lymph node metastasis of oral cancer: a retrospective study of 1466 cases

Abstract: Objectives Lymph node (LN) metastasis is a common cause of recurrence in oral cancer; however, the accuracy of distinguishing positive and negative LNs is not ideal. Here, we aimed to develop a deep learning model that can identify, locate, and distinguish LNs in contrast-enhanced CT (CECT) images with a higher accuracy. Methods The preoperative CECT images and corresponding postoperative pathological diagnoses of 1466 patients with oral cancer from our ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“… Precision Recall F1-score AUC 76.7% 82.1% 79.3% 0.79 3 Warin K. et al, 2022 [ 43 ] Thailand Clinical oral images (OPMDs) 600 images (70:10:20 for training, validation, and test) Annotated by three oral and maxillofacial surgeons N/A - Faster R-CNN - YOLOv4 100 epochs Batch size = 32 Learning rate = 0.00001 2 of GPU, TitanXP 12GB, Nvidia Driver: 450.102 and CUDA: 11.0. Precision Recall F1-score AUC 79.7% 81.0% 80.3% 0.74 4 Warin K. et al, 2022 [ 46 ] Thailand Clinical oral images (OSCC, OPMDs) 980 images (70:10:20 for training, validation, and test) Annotated by three oral and maxillofacial surgeons N/A - Faster R-CNN - YOLOv5 - RetinaNet - CenterNet2 1882 epochs Batch size = 8, 128 Learning rate = 0.001 15,000 and 20,000 iterations Tesla P100, Nvidia driver: 460.32 and CUDA: 11.2 (Nvidia Corporation, CA, USA) Precision Recall F1-score AUC 98.0% 92.0% 89.0% 0.91 5 Xu X. et al, 2023 [ 60 ] China CT images (OSCC) 5412 images (60:30:10 for training, validation, and testing) Annotated by a radiologist N/A - Mask R-CNN 10, 50, 100 epochs NVIDIA V100 GPU AP50 72.5% AUC Area under the curve …”
Section: Resultsmentioning
confidence: 99%
“… Precision Recall F1-score AUC 76.7% 82.1% 79.3% 0.79 3 Warin K. et al, 2022 [ 43 ] Thailand Clinical oral images (OPMDs) 600 images (70:10:20 for training, validation, and test) Annotated by three oral and maxillofacial surgeons N/A - Faster R-CNN - YOLOv4 100 epochs Batch size = 32 Learning rate = 0.00001 2 of GPU, TitanXP 12GB, Nvidia Driver: 450.102 and CUDA: 11.0. Precision Recall F1-score AUC 79.7% 81.0% 80.3% 0.74 4 Warin K. et al, 2022 [ 46 ] Thailand Clinical oral images (OSCC, OPMDs) 980 images (70:10:20 for training, validation, and test) Annotated by three oral and maxillofacial surgeons N/A - Faster R-CNN - YOLOv5 - RetinaNet - CenterNet2 1882 epochs Batch size = 8, 128 Learning rate = 0.001 15,000 and 20,000 iterations Tesla P100, Nvidia driver: 460.32 and CUDA: 11.2 (Nvidia Corporation, CA, USA) Precision Recall F1-score AUC 98.0% 92.0% 89.0% 0.91 5 Xu X. et al, 2023 [ 60 ] China CT images (OSCC) 5412 images (60:30:10 for training, validation, and testing) Annotated by a radiologist N/A - Mask R-CNN 10, 50, 100 epochs NVIDIA V100 GPU AP50 72.5% AUC Area under the curve …”
Section: Resultsmentioning
confidence: 99%
“…Deep learning-aided lymph node prediction has been enrolled in some solid tumours. 30 , 31 In the present study, we built a CNN model based on DCE-MRI images of primary lesions to predict SLN and NSLN metastasis successively. Firstly, for SLN prediction, the CNN model winded up with an AUC of 0.885 in the external test set 1.…”
Section: Discussionmentioning
confidence: 99%
“…Although not used in this study, MRI diffusion-weighted imaging and apparent diffusion coefficient may add new diagnostic criteria [42]. In recent years, research on diagnosing lymph nodes using artificial intelligence and radiomics has been reported, and this may be useful in diagnosing lymph node metastasis in the future [43,44].…”
Section: Discussionmentioning
confidence: 99%